Songkhramodopsis gen. nov., a new genus of Cypridopsinae (Crustacea: Ostracoda) from Thailand - Savatenalinton, Sukonthip (Zootaxa, 2023)
A new genus and species of subfamily Cypridopsinae Kaufmann, 1900, Songkhramodopsis meischi gen. et sp. nov., is described from the Lower Songkhram River Basin, Thailand. The prominent diagnostic characters of the new genus mainly exist in antennula (A1), antenna (A2) and third thoracopod (T3): the six-segmented A1, the strongly serrated claw G2 on the female A2, the large aesthetasc Y with remarkably large and striated third section and the completely separated terminal segment of T3. The A1 with six segments, together with the distinctive morphology of aesthetasc Y, have been recognized for the first time in the Cypridopsinae. A new tribe, Songkhramodopsini trib. nov., is also erected to accommodate this exceptional new genus and species. The new taxon is also characterized by the left valve overlapping the right valve, the anterior and posterior inner list on both valves, the widely inwardly displaced posterior selvage on right valve, the bifurcate-like tip of an apical ventral seta on A1 first segment, the absence of d1 seta on second thoracopod (T2), the divided penultimate segment of T2, the female caudal ramus with cylindrical base, the very small number of spiny whorls of Zenker organ. A key to tribes of Cypridopsinae is provided.